Electrochemical vicinal oxyazidation of α-arylvinyl acetates - Li, Yi-Lun; Shi, Zhaojiang; Shen, Tao; Ye, Ke-Yin (Beilstein Journal of Organic Chemistry, 2022)
α-Azidoketones are valuable and versatile building blocks in the synthesis of various bioactive small molecules. Herein, we describe an environmentally friendly and efficient electrochemical vicinal oxyazidation protocol of α-arylvinyl acetates to afford diverse α-azidoketones in good yields without the use of a stoichiometric amount of chemical oxidant. A range of functionality is shown to be compatible with this transformation, and further applications are demonstrated.
Keywords: azide; azidoketone; electrosynthesis; enol acetate; radical